Simple Extraction and Molecular Weight Characterization of Fucoidan from Indonesian Sargassum sp. - Junaidi, Lukman (Biopropal Industri, 2013)
Fucoidan is a complex polysaccharide compounds found in brown algae. Fucoidan exhibits various biological properties for disease prevention. There are various methods used to extract fucoidan from brown algae, such as using ethanol, acetone, HCl and microwave. This research aims to extract and characterize fucoidan from Sargassum sp. using simple methods with the variables on extracting solutions, temperature and time of extraction. Extraction solution used were water and HCl. Ttemperature used was 50°C, 70°C and 100°C  using 1, 2 and 4 hours. The result showed that the highest extraction yield was obtained from the extraction by water with 100°C and 4 hours of extraction. Fucoidan extracted by water has molecular weight of 57.77 kDa and 2.71 kDa, while fucoidan extracted by HCl has molecular weight of 46.43 kDa and 3.38 kDa. The proportion of high molecular weight fucoidan extracted by water was 52.24% compared with HCl was 44.10%.